PROFIL USAHA SALON KECANTIKAN DI KOTA PADANG - RR, Maylina; Rostamailis, Rostamailis; Hayatunnufus, Hayatunnufus (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
In the development of a beauty parlor in the city of Padang growing rapidlybut in some unknown operational problems. This study aimed to describe theprofile of a beauty parlor in the city of Padang. This type of research isquantitative descriptive. The research population is all employees, amounting to90 people and all sampled (total sampling). Data collection technique is using aquestionnaire (questionnaire) are adjusted in the form of a Likert scale andGuttman scale that have been tested for validity and reliability. Data wereanalyzed using the percentage formula and categorizing. Based on the results ofresearch on the type of skin beauty care categories. type of hair beauty services ata very good category. Based on the quality of human resources on the acquisitionof competence in the field of beauty expertise acquired 71% of data is a graduateSMA / SMK general, 28% of graduates of vocational Tata Beauty is only 1% TataBeauty Diploma graduates, 47% attended a course skin care, while the formalstatus of the course 29% 62% non-formal. Salon business personnel workaccording to the division of tasks in the medium category with a percentage of78%. 72% of business personnel maintain the beauty salon Health and Safety atWork in the medium category. 62%. Personnel beauty salon business has apersonality according to professional ethics in the unfavorable category. 70% havea beauty salon business personnel hygiene and personal appearance in the mediumcategory. Judging from the infrastructure business has a beauty salon equipmentstandard work on unfavorable category, have the appropriate building standards inmiddle category, meet clean water standards that are in either category.Kata Kunci : Profil, Usaha Salon Kecantikan